(untitled) (Revista Brasileira Multidisciplinar, 2020)
Background: Tuberculosis (TB) affects 1/3 of the world’s population and about 10 million people develop TB each year, resulting in 2 million deaths. Objectives: The main goal of this work is to present a study of the epidemiological profile of TB in Araraquara, Brazil and to compare the epidemiological profile with the number of the diseases in the world, Americas, Brazil and the State of São Paulo. Methods: Surveys and information were collected from World Health Organization (WHO ) annual report, Brazilian Ministry of Health, Secretary of the State of São Paulo, Municipal Health Department and the Special Healthcare Service of Araraquara (SESA). The period from 2012 to 2017 was analyzed considering the projections of the WHO goals to the end of TB from 2015 to 2035. Results: All data presented, except for the city of Araraquara, are above the projection required by OMS. Although slightly below the projection cited above, Araraquara is on track to reduce the incidence of TB to the point of eradicating the disease. Conclusions: Current low TB infection levels in Araraquara combined with factors such as one of the highest Human Development Index (HDI) in the country, the existence of a sanatorium specialized for treatment of the disease, public policies and an efficient information network about TB can explain the results and make Araraquara a model in the fight against the disease at national level. The city seems to be able to eradicate the disease within or even before OMS deadline.